Synthesis of Titanium Oxycarbide through Carbothermal Reduction of Titanium Dioxide Nanoparticles and Renewable Biopolymers. (27th April 2016) - Flach, Joshua Paul; Figueiredo de Lima, Paulo Henrique; Sparks, Joshua Craig; Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : The goal of this is study is to explore the feasibility of a sustainable method of titanium oxycarbide synthesis through carbothermal reduction of a biopolymer composite. The reaction was studied at different temperatures in vacuum environments and at multiple TiO2 :C ratios in order to determine how these parameters affect the formation of titanium oxycarbide. The results indicate that both the heat treatment and the carbon ratios have a significant impact on the O/C ratio, and therefore, molecular composition and crystal structure of the titanium oxycarbide. The use of renewable biopolymers as a carbon source in the synthesis of oxycarbide can serve as an inexpensive, yet effective alternative to petroleum based sources.